Elderly satisfaction evaluation with the use of outdoor fitness equipment - Sena de Castro e Silva, Renan; Tatiane de Barros Macêdo Veloso, Isis (DAT Journal, 2021)
This work presents the results of a master’s dissertation research, which aimed to assess the satisfaction of the elderly regarding the use of fitness equipment in outdoor gyms. The case study of this research is the Parque da Criança, in the city of Campina Grande (PB). Observational and interactional methods were used, and the elderly users were divided into two groups: Group 1 (non-experienced) and Group 2 (experienced) after agreeing to sign a TCLE (Free and Informed Consent Form). Forms and usability tests such as the SUS (System Usability Scale) and the DS (Semantic Differential) were applied as instruments. The study evidenced that the more the public is used to the equipment, the higher the satisfaction rates are, and that the impressions can vary as the user gets used to the equipment, whether in positive or negative aspects. For both experienced and non-experienced users, the equipment is considered satisfactory concerning the verified aspects of safety, usability, comfort, intuitiveness and pleasure.